Pengaruh Citra Merek, Harga Dan Gaya Hidup Terhadap Keputusan Pembelian Hp Iphone (Studi Kasus pada Pengguna Iphone di Kota Malang) - Rafiq, Hasfito; Wahono, Budi; Khalikussabir, Khalikussabir (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to see whether brand image, price, and lifestyle have a simultaneous or partial effect on the decision to purchase an iPhone in Malang City. This study applies a quantitative method with the research method used is a survey. In the context of this study, the population consists of iPhone users in Malang City. Based on BPS data, the population in Malang City in 2023 was 847,182. The sample in this study were consumer users who bought iPhone products in Malang Raya City. The population is not known for sure, so the sample size used, according to Malhotra's opinion, 5 x 16 indicators is 80 respondents. The results of the study show that the variables Brand Image, Price and Lifestyle have a simultaneous effect on the decision to purchase an iPhone. Brand Image has an effect on the decision to purchase an iPhone. Price has an effect on the decision to purchase an iPhone. Lifestyle has a positive and insignificant effect on the decision to purchase an iPhone. Keywords : Brand image, Price, Lifestyle and Decision to purchase